Simplify. Express your answer using positive exponents.

(4y^7)(5y)

1 answer

To simplify the expression \((4y^7)(5y)\), you can first multiply the coefficients (the numerical parts) and then combine the like terms (the \(y\) terms) using the laws of exponents.

  1. Multiply the coefficients: \[ 4 \times 5 = 20 \]

  2. Combine the \(y\) terms: \[ y^7 \times y = y^{7+1} = y^8 \]

Now, putting it all together, we get: \[ (4y^7)(5y) = 20y^8 \]

Thus, the simplified expression is: \[ \boxed{20y^8} \]